1969
DOI: 10.1111/j.1471-4159.1969.tb06444.x
|View full text |Cite
|
Sign up to set email alerts
|

RESPIRATION IN VITRO OF SYNAPTOSOMES FROM MAMMALIAN CEREBRAL CORTEX

Abstract: Abstract— —(1) The respiratory properties of synaptosomes and mitochondria from mammalian cerebral cortex are compared. (2) Synaptosome showed high and linear respiration with glucose and pyruvate as substrates in Krebs‐Ringer media. Mitochondria showed such respiration only with pyruvate as substrate in media lacking Na and high in K and phosphate. (3) Exposure of synaptosomes to hypotonic media caused loss of lactate dehydrogenase (LDH) and protein, and respiration diminished and became non‐linear. (4) Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
82
0

Year Published

1972
1972
1981
1981

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(94 citation statements)
references
References 21 publications
12
82
0
Order By: Relevance
“…As can be seen from Bradford (1969) and containing 25,uCi of 32P1 in a final volume of 1 ml. One of the pair was washed four times with excess of unlabelled cold medium and incubated for 10min in the same medium.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from Bradford (1969) and containing 25,uCi of 32P1 in a final volume of 1 ml. One of the pair was washed four times with excess of unlabelled cold medium and incubated for 10min in the same medium.…”
Section: Resultsmentioning
confidence: 99%
“…This is a value which is comparable with the rate of respiration of more highly purified synaptosomal preparations (Bradford, 1969). Table 1 presents values for the radioactive labelling of the crude synaptosomal fraction (P2) after 7.5 and 15min at 37°C in vitro and the corresponding rate of incorporation of radioactivity into the phospholipids of the D fraction after 15min, based on the specific radioactivities of the labelled compounds used.…”
Section: Radioactive Labelling Ofp2 Fractionsmentioning
confidence: 71%
“…This was a reasonable finding, as extrasynaptosomal microsomal and mitochondrial fractions were deprived of substrates and of cofactors which are essential for phospholipid turnover, by the rudimentary nature of the Krebs glucose incubation medium used. In the absence ofsuitable substrates for mitochondrial respiration and because of the concentration of Na+ in the medium (Bradford, 1969), no significant ATP generation outside the synaptosomes would also be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, numerous studies have shown that synaptosomes (pinched-off nerve ter minals isolated from brain homogenate) resemble intact tissue in transport (2,3) and metabolic processes (4,5), and thus syn aptosomes should afford on excellent model system for examining calcium disposition at the nerve endings.…”
mentioning
confidence: 99%